1, 2‐Silyl migration in 1‐halonaphthalenes catalyzed by I2. Issue 4 (11th September 2018) - Shimizu, Tomomi; Morisako, Shogo; Yamamoto, Yohsuke; Kawachi, Atsushi
Abstract: 1‐Halo‐8‐hydrosilylnaphthalenes undergo 1, 2‐silyl migration to form 1‐halo‐7‐silylnaphthalenes. The influence of the substituents on the silicon atom, the solvent effect, and the D‐labeling experiments are investigated. The migration process may include four steps: (a) generation of acid (HI) by the reaction of the hydrosilane with I2, (b) protonation of the naphthalene ring, (c) silyl group migration in the protonated intermediate, and (d) deprotonation of the naphthalene ring.